REAKSI PASAR TERHADAP PERISTIWA PENGUMUMAN KENAIKAN SUKU BUNGA BANK SENTRAL AMERIKA SERIKAT 17 DESEMBER 2015 (STUDI EMPIRIS TERHADAP PERUSAHAAN - PERUSAHAAN YANG TERGABUNG DALAM INDEKS LQ 45) - B31112053, Edi Mulyono (Jurnal Manajemen Update, 2016)
Information is aa primary need for the capital market?s investors. Economic events overseas that contain relevant information for investors will cause the market reaction and reflected by changes in stock prices and changes in trading volume activity. This reaction can be measured by abnormal return and trading volume activity changes.Thisresearch is an event study which is aimed to findempirical evidence of the Indonesian capital market reaction to economic events the announcement of The Feed-rate increase. In addition, this study attempted to examine the extent to which the implementation of the efficient market hypothesis in the Indonesia Stock Exchange. The population in this study are all stocks included in LQ45 during the study period. While the selection of the sample taken through purposive sampling with criteria for stock companies that do corporate action during the event period. One t test (t-test) was used to test whether the average abnormal return significant value on the day around the events that prove the existence of market reaction. While testing the difference between two average - average abnormal return and trading volume activity was used to test the reaction of the difference between before and after the occurrence of The Feed-rate increase. The results of the study significant abnormal return on a five-day event period, indicating that the market reacts to economic events and socio-political events. But the results of different test average abnormal return period before and after the event did not show significant results. So also with the different test results of the average trading volume activity did not show significant results. Keywords : the content of the relevant information , the market reaction , event study , abnormal return , trading volume activity.